PELATIHAN MICROSOFT OFFICE DI SMK N 2 BALIGE - Susanti Samosir, Hernawati; Hutapea, Oppir; Manurung, Philippians; Ray Hutauruk, Andi; Sinambela, Amsal; Partumpoan Siahaan, Kevin; Sinaga, Hasan; Albi Pulo S, Samuel; Tomfie Bukit, Kenan; Panjaitan, Claudia (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Basic Ms Office knowledge is one of the most general and commonly used in industry or companies from the lowest level to the hight type of industry. However, in Toba area itself, mentioned as SMK N 2 Balige which located in Balige, North Sumatra which all students do not familiar with Ms Office usage. There are no special subjects that can support other subjects according to the major, namely basic Microsoft Office science. As mentioned by the headmaster of SMK N 2 Balige that the graduations are only 30 person(10%) got accepted in industry every year. Seeing this issue, IT Del has a responsibility to increased student performance which will be accepted in industry during the graduation timeline every year. IT Del as an educational institution operating in the field of technology can of course provide assistance in the form of training that will help these students to have the skills of Ms. Offices that are needed in the industrial company. The training carried out at the school is Ms Word, Ms Excel, Ms Power Point. Each is given a module that describes the real work in the industrial world so that students are expected to be able to adapt to the learning modules provided. These three materials are taught in parallel and alternately so that all students have the opportunity to discuss the training module as a whole. The assessment technique is seen from the student's speed in working on the example questions given and being able to solve them well and correctly. The average ability of students in working on Ms Word questions is 59.33, Ms Excel 75.78 and Ms Power Point 76.44. In this training, 3 students were obtained with the highest scores from all students, namely 270, 265 and 260. From the results of the training carried out, it can be seen that the students of SMK N 2 Balige were enthusiastic in participating in Ms. Office.